FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBERDAYAAN GENDER (IDG) KOTA MAGELANG TAHUN 2011-2021 - Rusli, Aldhi Sahara; Magna, Merlin Swantantamalo (EVOKASI: Jurnal Kajian Administrasi dan Sosial Terapan, 2023)
Magelang City is categorized as an area with a high Gender Empowerment Index (IDG) score, but there are still gender equality issues. The gap in average years of schooling between men and women, differences in the labor force participation rate of men and women, and women’s representation in parliament is still below 30%. This study aims to determine the factors influencing IDG in Magelang City from 2011-2021. This study uses quantitative research methods with multiple linear regression analysis methods. Multiple linear regression analysis was conducted to determine the magnitude of the influence of the average length of schooling variable, labor force participation rate, and women in parliament on the IDG variable. The data used in this study are data from the Magelang City Central Bureau of Statistics and the Central Java Central Bureau of Statistics. This study found that the factor of women in parliament has a significant effect of 94.6% on IDG, and other factors influence the remaining 5.4%. The magnitude of the influence of the variable of women in parliament This indicates that most of the increase or decrease in IDG in Magelang City is influenced by women’s representation in parliament. Women’s representation in parliament has a significant effect on the IDG of Magelang City, which means that women have an influence on the political policy-making process in Magelang City. Women’s involvement in decision-making can fight for issues related to women’s interests.